Analisis Kualitatif Dokumen Rekam Medis Kasus Aborsi Tidak Lengkap dalam Aborsi Spontan dengan Metode Hatta Di RSUD Kabupaten Ciamis Tahun 2016 - Dila Kardila; Diana Barsasella (STIKes Persada Husada Indonesia, 2018)
Medical records are important notes for a health institution in carrying out service organization. Every hospital must have a medical record work unit in providing health data in the hospital for various prominence (RI Law No. 44 Year 2009 Article 29). Method of study was Qualitative Descriptive with Cross Sectional approach of 60 medical records documents on Incomplete Abortion inpatient cases. Incomplete Abortion Qualitative Administrative Analysis result showed 50 (83,3%) cases of clarity of problems and conditions or diagnosis, 37 (61,7%) consistent input, 49 ( 81,7%) service reasons, 37, (61,7%) informed consent, 31 (51,7%) up-to-dates, 55 (91,7%) readable text based on 3 patients, 43 (71,7%) standard abbreviations, 60 (100%) satire avoidance, 53 (88,3%) gapless fulfilment, 60 (100%) usage of standard ink and 50 (88,3%) obvious notes in the order of service. Incomplete recording of 60 (100%) inormtion on compensation and guarantor of costs. Medical qualitative analysis on Incomplete Abortion cases with highest complete record on age of mothers 60 (100%) with score of 4 to the information “Yes”, information “Not The Case” 60 (75,0%) to Blood Pressure statement, information “No” 60 (76,7%) haemorrhaging observation statement, “No Information” 60 (100%) to smoking and alcoholism, anemic haemorrhaging, torn cervix and perforation statements. Frequency of medical record documents on Incomplete Abortion cases can be said to be complete, based on the high level of completeness of administrative and medical notes. Incomplete records occurred in the operation and anesthesia notes while every patient is given curettage action.